Differences of Tumor Size Measured by Ultrasonography and Magnetic Resonance Imaging Compared to Pathological Tumor Size in Primary Breast Cancer - Young Hun Kim; Yoo Seok Kim (Journal of Surgical Ultrasound, 2022)
Background : : Preoperative measurement of the tumor size is essential for deciding on a treatment plan for breast cancer. In particular, in a neoadjuvant setting, the treatment plan is based on preoperative clinical staging. This study evaluated the differences in tumor size measured by ultrasonography and magnetic resonance imaging (MRI) compared to the pathological tumor size.Methods : : This study reviewed the electronic medical records of patients with primary breast cancer who underwent surgery between 2014 and 2021. The clinicopathologic data, including ultrasonographic and MRI findings, were collected. Bland-Altman analysis was used to compare the differences in the tumor size between the imaging modalities and pathological tumor size.Results : : The tumor size was underestimated significantly by ultrasonography. On the other hand, there were not significant differences in the correlation.Conclusion : : The preoperative evaluation, including ultrasonography and MRI, helps predict the tumor size accurately in primary breast cancer.